L’analyse du discours du Président Massoud Barzani : le cas du communiqué du 16 mai 2016 - Zakarya Mohammed Salim (Zanco Journal of Humanity Sciences)
One hundred years ago, the Skyes-Picot agreements sealed the fate of Kurdistan by dividing it into four parts. On May 16, 2016, President Barzani returned to the consequences of this agreement in a written statement related to the ethos, pathos and logos, elements of rhetoric peculiar to political discourse. The crimes perpetrated against the Kurdish people find their echo in what Patrick Charaudeau, in his book «Lediscours politique. Les  masques du pouvoir "(2005) calls social disorder. Presented as a state of affairs or as a potential state, it tends in the first case to persuade the public of the presence of the evil, and in the second case to generate the fear of the possible existence of the evil. Barzani poses as the savior of the Kurdistan people, the very embodiment of what Charaudeau calls saving solution, that is to say the representation of a defender proposing measures to annihilate evil.